PENGEMBANGAN MEDIA SMART BOX RULE HOUSE TERINTEGRASI MODEL PJBL UNTUK MENINGKATKAN KETERAMPILAN KOLABORASI PEMBELAJARAN PENDIDIKAN PANCASILA KELAS 4 SD - Dilalatun Navida, Fiora; Mawardi (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aimed to develop and determine the feasibility, practicality, and effectiveness of the Smart Box Rule House learning media integrated with the Project Based Learning (PjBL) model to improve fourth-grade elementary students’ collaboration skills in Civic Education. This research employed a Research and Development (R&D) approach using the ADDIE model, which consists of analysis, design, development, implementation, and evaluation stages. The subjects were 47 fourth-grade students from three elementary schools in Semarang Regency, Indonesia, along with experts in media, material, and instructional design as validators. Data were collected through validation sheets, questionnaires, observations, and interviews, and analyzed using descriptive quantitative and qualitative techniques. The results showed that the media was highly valid, with validation scores of 100% (media), 88% (material), and 100% (instructional design). The practicality test indicated very positive responses from teachers (94.67%) and students (96.53%). Furthermore, most students achieved high and very high levels of collaboration skills, including working productively, respecting others, compromising, and sharing responsibilities. Therefore, the Smart Box Rule House integrated with PjBL is feasible, practical, and effective in enhancing students’ collaboration skills through interactive and project-based learning.